PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI ORGAN PENCERNAAN MANUSIA KELAS V SDN 3 JANGKURANG - Siti Sholiha Nurfaidah; Elis Julaeha; Azis Lukman Praja (STKIP Subang, 2022)
This research is motivated by the condition of students abilty to master science material, aspecially in the material human digestive organs in grade V SD Negeri 3 Jangkurang which is still low. This is because teachers still use convensional learning methods in the learning process. So that student do not get the opportunity to understand the subject matter. The problem in this research is “What Is The Aplplication Problem Based Learning Models Can Improve The Learning Outcomes Of Grade V Students SDN 3 Jangkurang On The Material Of Human Digestive Organs”. Essentially science learning science learning is the result human activitiesin the form of knowledge, organized ideas and concepts about natural environment, derived from experience through a series of scientific processes among others investigation, of the preparation and testing of ideas. The methods used in this study is Classroom Action Research with research subjects are SDN 3 Jangkurang Students, Jangkurang Village, Kadungora District, Garut Subdistrict. With the number of student are 15 peoples. Consisting of 6 male students and 9 female students. This research consist of 3 cycles. The implementation of each cycle is directed at learning activities using the models Problem Based Learning (PBL) which is used as an science learning plan on human digestive organs. From the learning process that has been carried out the result of science learning are obtained, which shows an increase in each cycle starting from cycle I, II, and III. In cycle I there were ten students (67 %) who scored <70 , and five students (33%) who scored > 70. In cycle II there were five students (33%) who scored < 70, and ten students (67%) who scored > 70. In cycle III there were four students (67 %) who scored <70 , and eleven students (73%) who scored > 70. The Aplplication Problem Based Learning Models can improve the learning outcomes.